The eukaryotic linear motif resource – 2018 update. Issue Volume 46:Issue D1(2018) (10th November 2017) - Gouw, Marc; Michael, Sushama; Sámano-Sánchez, Hugo; Kumar, Manjeet; Zeke, András; Lang, Benjamin; Bely, Benoit; Chemes, Lucía B; Davey, Norman E; Deng, Ziqi; Diella, Francesca; Gürth, Clara-Marie; et al.
Abstract: Short linear motifs (SLiMs) are protein binding modules that play major roles in almost all cellular processes. SLiMs are short, often highly degenerate, difficult to characterize and hard to detect. The eukaryotic linear motif (ELM) resource (elm.eu.org ) is dedicated to SLiMs, consisting of a manually curated database of over 275 motif classes and over 3000 motif instances, and a pipeline to discover candidate SLiMs in protein sequences. For 15 years, ELM has been one of the major resources for motif research. In this database update, we present the latest additions to the database including 32 new motif classes, and new features including Uniprot and Reactome integration. Finally, to help provide cellular context, we present some biological insights about SLiMs in the cell cycle, as targets for bacterial pathogenicity and their functionality in the human kinome.